TIPE EMBRIONI PLASMA NUTFAH MANGGA (Mangifera sp.) LANDRACES BALI - Putu Suwardike; I Putu Parmila; P Shantiawan Prabawa; Made Suarsana; Jhon Hardy Purba (Fakultas Pertanian, Universitas Janabadra, 2023)
The embryonic type of mango accession needs to be known because it has an important role in its development, especially in the propagation of mango plants. Polyembryonic mango cultivars have the potential to produce zygotic embryos that can show morphological and genetic diversity. Research with the aim of knowing the embryonic type of Bali landraces mango germplasm as the basis for its development, especially in selecting cultivars that have potential as rootstocks, was carried out in Banyuning Village, Singaraja in July-September 2022. A total of 34 landraces accessions and 10 non-landraces Bali came from Buleleng, Karangasem, Klungkung and Badung districts were used as research materials, involving 10 seeds per accession each. The seeds were sown in polybags filled with river sand. Germinated seeds were removed from the seedling, the number of sprouts that grew on each seed was counted. The results showed that there were monoembryonic and polyembryonic types of Bali landraces accessions. A total of 32 accessions or 94.12% of Bali landraces accessions showed the polyembryonic type, and 2 landraces accessions, namely Pakel Sibetan and Pakel Sulangai showed monoembryonic. Introduced accessions, such as Brazil, Parkit, Shaigon, and Apel are classified as monoembryonic.INTISARITipe embrioni aksesi mangga perlu diketahui karena memiliki peran penting dalam pengembangannya, khususnya dalam perbanyakan tanaman mangga. Kultivar mangga poliembrionik berpotensi menghasilkan embrio zigotik yang dapat menunjukkan keanekaragaman morfologi dan genetik. Penelitian dengan tujuan untuk mengetahui tipe embrioni plasma nutfah mangga landraces Bali sebagai dasar pengembangannya, khususnya dalam memilih kultivar yang berpotensi sebagai batang bawah telah dilakukan di Kelurahan Banyuning, Singaraja pada Juli-September 2022. Sebanyak 34 aksesi landraces dan 10 aksesi non landraces Bali yang berasal dari Kabupaten Buleleng, Karangasem, Klungkung dan Badung digunakan sebagai bahan penelitian, melibatkan masing-masing 10 benih per aksesi. Benih disemai dalam polybag berisi media pasir sungai. Benih berkecambah dikeluarkan dari semaian, dihitung banyaknya kecambah yang tumbuh pada setiap benih. Hasil penelitian menunjukkan, tipe embrioni aksesi landraces Bali ada yang monoembrioni maupun poliembrioni. Sebanyak 32 aksesi atau 94,12% aksesi landraces Bali menunjukkan tipe poliembrioni, dan 2 aksesi landrases yaitu Pakel Sibetan dan Pakel Sulangai menunjukkan monoembrioni. Aksesi introduksi, seperti Brazil, Parkit, Shaigon, dan Apel tergolong monoembrioni.